1975
DOI: 10.1029/ja080i031p04237
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the magnetopause energetic electron layer

Abstract: Three years of Imp 5 data show that the magnetopause layer of energetic electrons was present during 227 of 230 orbits over this period and extends along the magnetopause from geomagnetic latitudes as low as 40° to latitudes corresponding to the polar cap. It also exists at the boundary between the magnetosheath and the polar cusp region. The data show that the integral energy spectrum of these electrons (Ee > 18 keV) varies greatly with the planetary Kp index and hardens with increasing Kp values. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…1) the outbound pass through the magnetosheath in late October 1983 at -100 Re downtail, we estimate from close examination of the data that the last electron burst was detected a distance of -5-6 Re from the last magnetopause crossing. These observations are consistent with previous reports of a "layer" of streaming energetic electrons extending 1-5 Re outside the magnetopause and observed to at least 40-60 Re downtail (Meng and Anderson, 1975;Baker and Stone, 1978). Our observations suggest that this layer extends to at least 200 Re down the tail, albeit with a considerably reduced electron intensity (Fig.…”
Section: Electron Bursts In the Magnetosheathsupporting
confidence: 83%
“…1) the outbound pass through the magnetosheath in late October 1983 at -100 Re downtail, we estimate from close examination of the data that the last electron burst was detected a distance of -5-6 Re from the last magnetopause crossing. These observations are consistent with previous reports of a "layer" of streaming energetic electrons extending 1-5 Re outside the magnetopause and observed to at least 40-60 Re downtail (Meng and Anderson, 1975;Baker and Stone, 1978). Our observations suggest that this layer extends to at least 200 Re down the tail, albeit with a considerably reduced electron intensity (Fig.…”
Section: Electron Bursts In the Magnetosheathsupporting
confidence: 83%
“…During the time period between 18:20 and 18:30 UT on 27 February 2006, the flux distribution between 40 and 400 keV is represented by a power law with a slope of α=−1.80 where Flux∼ A · E α , E is energy and A is a constant. Meng and Anderson (1975) measured a power law with a slope of α=−1.94±0.19 for electrons downstream along the magnetopause. It's likely that local acceleration of electrons in the cusp can contribute to the electron population flowing downtail along the magnetopause.…”
Section: Potential Magnetospheric Impactmentioning
confidence: 99%
“…[ 1977] found evidence for •< 10% net tailward flow of the electrons. Meng and Anderson [1975] presented electron data (E > 18 keV to E > 120 keV) at high latitudes near the dayside magnetopause and within the polar cusp region. It was again found that the magnetopause layer was persistently present.…”
Section: Introduction Energetic Electrons Near the Magnetopause Have mentioning
confidence: 99%